(untitled) (Fiep Bulletin - online, 2014)
The Pataxó Indians Games are a cultural event inspired in their culture and traditions, and represents a form of affirmation of their identity. The game second Caillois (1990) can be classified as Agôn, Alea, Mimicry and Ilinx and when analyzing the Pataxó Indians Games, it has a strong presence of the agonístic factor, with characteristic of etno-sport due striking presence of their traditions in more different events.